2020
DOI: 10.24996/ijs.2020.61.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Geological Structures on Rock Slope Stability in The NW Nose (Plunge ) of Surdash Anticline, Sulaimaniya/ NE Iraq

Abstract: The road network in Surdash anticline is considered as an important road network connecting lower Dukan town with the touristic upper Dukan town . Dukan lake plays an important role in the social and economic activities of Dukan town and the surrounding areas. For assessing the stability of the rock slopes in the area, 9 stations were selected along the upper Dukan road on both sides of Surdash anticline, and their stability was evaluated by the kinematic analysis using DIPS V6.008 software.Kinematic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…The age of this zone indicates Early Turonian, which is equivalent to that of Abdel-Kareem et al (1996) [29], [17], and the older part of Globotruncana helvetica zone of Youkhanna (1976) [9], Postuma (1971) [16]. this zone is also equivalent to that proposed by Lawa and Al-Khafaf (2022) [6], Hussain and Al-Sheikly (2015) [30], and Al-Khafaf (2014) [31], also this zone corresponds to the older part of Marginotruncana helvetica zone of Ghafor et al (2004) [32], Ghafor (1993) [33].…”
Section: Biostratigraphic Zonationssupporting
confidence: 58%
“…The age of this zone indicates Early Turonian, which is equivalent to that of Abdel-Kareem et al (1996) [29], [17], and the older part of Globotruncana helvetica zone of Youkhanna (1976) [9], Postuma (1971) [16]. this zone is also equivalent to that proposed by Lawa and Al-Khafaf (2022) [6], Hussain and Al-Sheikly (2015) [30], and Al-Khafaf (2014) [31], also this zone corresponds to the older part of Marginotruncana helvetica zone of Ghafor et al (2004) [32], Ghafor (1993) [33].…”
Section: Biostratigraphic Zonationssupporting
confidence: 58%
“…The sequences of Late Campanian-Maastrichtian were affected by the obduction zone and closure of the Southern Neo-Tethys, and flysch derived from erosion of the Arabian plate flanking thrust belt [3]. The studied area is located in the high fold zone of an unstable shelf of the northeast Arabian plate [4]. This study focused on determining the concentrations of major and some trace elements in carbonate rocks because of their importance in knowing the paleoenvironmental conditions and diagenetic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Mohammed et al (2019) extracted and delineated Pira Magroon alluvial fans by using a remote sensing. Hussien et al (2020) assessed the stability of the rock slopes in the northwestern plunge of Surdash Anticline, using Kinematic analysis, and showed that some stations suffer possibly from planer and wedge sliding whereas others are stable. Forti et al (2021) conducted a geomorphological study in the Kurdistan Region and discussed different geomorphological features.…”
Section: Introductionmentioning
confidence: 99%